Specification framework for privilege escalation testing in Linux systems - Martins, Gustavo Zanzin Guerreiro; Campiolo, Rodrigo (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on Cybersecurity, 2025)
This work proposes the especification and evaluation of a framework focused on privilege escalation in Linux systems, targeting entry-level professionals. The framework’s definition employs a narrative review guided by specific criteria and an adapted ontology to model its initial structure. An experiment will assess the framework’s impact on reducing the omission of attack vectors during security assessments. The framework is expected to contribute both to the operational systematization of privilege escalation procedures and to the technical training of beginners.